Empowering Teratai 49 As-Sakinah Elderly Health Post Management Toward Healthy Independent And Prosperous Seniors - Ulya Anisatur Rosyidah; Dwi Yunita Haryanti; Juariyah Juariyah; Nely Ana Mufarida (TRANSFORMASI : JURNAL PENGABDIAN PADA MASYARAKAT, 2026)
The increasing elderly population in Indonesia necessitates strengthening community-based health services through enhancing the capacity of elderly integrated health post (Posyandu Lansia) management. The Teratai 49 As-Sakinah Elderly Integrated Health Post in Cakru Village continues to face challenges in program management, coordination among administrators, and the development of sustainable activity plans. This community service program aimed to empower the administrators of the Elderly Integrated Health Post through an integrated empowerment model consisting of health education, training, continuous mentoring, organizational management strengthening, and cross-sector collaboration to improve the quality of health services for older adults. The program was conducted from June to August 2025 and involved 10 administrators of the Elderly Integrated Health Post. Program evaluation was carried out using pre-test and post-test assessments to measure knowledge improvement, observational checklists to assess practical skills, and monitoring of elderly participation before and after the intervention. The results demonstrated that the mean knowledge score increased from 50.9 to 85.3, representing a 67.6% improvement with a normalized gain (N-gain) score of 0.70 (high category). In addition, the number of active elderly participants increased from 28 to 41 individuals, while attendance rates improved from 55% to 85%. The success of the program was supported by a participatory approach, continuous mentoring, and collaboration among the Elderly Integrated Health Post administrators, the village government, and the community health center (Puskesmas). This program contributed to strengthening the capacity of the Elderly Integrated Health Post administrators in managing community-based elderly health services and produced an empowerment model with the potential to be replicated in other Elderly Integrated Health Posts to support healthy, independent, and prosperous ageing.